The Springfontein prospect : a case study of a tertiary age epithermal hot spring deposit in the Eastern Cape - Nichols, Richard Lionel (Rhodes University, Faculty of Science, Department of Geology, 1991)
The Springfontein Prospect is a Tertiary aged epithermal Hot Spring deposit that was investigated for precious metal mineralisation. It is located some 14 kilometres due west of East London (Cape Province), within Beaufort Group sediments and Karoo dolerite. Prior to the work described in this case study, the location was known for it's abundant plant fossils and barite mineralisation. A gossan sample collected near the main barite vein returned 1,07 g/t Au and 26,6 g/t Ag. Remote sensing studies of the site revealed a set of north-south lineaments paralleling the barite vein system. Geophysical surveys confirmed this orientation and revealed an extensive alteration system underlying the prominent sinter terrace. A detailed soil geochemical survey returned elevated values in the classical epithermal gold mineralisation element suite (Rg, Tl, As, Bi, Sb, Te, Mo, Ba and Pb - Bonham, 1986). Trenching of geochemical anomalies revealed zones of intense argillic alteration and vein stockworks). Four percussion and three diamond drill holes intersected a 'feeder-fissure' system of veins, alteration and brecciation, but failed to repeat gold levels seen at surface. Mineralogical and petrographic studies of the cores determined temperatures of formation of important indicator minerals (e.g. adularia and zeolites). Litho-geochemical work revealed mercury (and thallium) to be most elevated in the feeder systems. Stratigraphic and paleontological observations determined that the Springfontein Tertiary deposit was clearly different to the other siliceous (silcrete) units that crop out in the Eastern Cape region. A number of distinguished visitors to the prospect, with epithermal deposit experience, confirmed that the characteristics and dimensions of the system is within those of mineralised deposits elsewhere. A brief review of current epithermal models are presented. The conceptual geological model for the Springfontein prospect evolved through the exploration programme. The final consensus is that it best fits Bonham's (1986) alkalic model and the Tertiary epithermal event was sustained by rifting associated with the break-up of Gondwanaland.
Keywords: Hot springs -- South Africa -- Eastern Cape